A taxonomic revision of the propaguliferous species of Pohlia (Bryaceae, Bryophyta) in Latin America - Suarez, Guillermo Martin (2011)
A taxonomic revision of the propaguliferous species of Pohlia (Bryaceae, Bryophyta) in Latin America. A taxonomic and descriptive study of the propaguliferous species of the genus Pohlia with axillary and rhizoidal bulbils from Central and South America is presented. Six species with axillary gemmae and one with rhizoidal tubers are recognized in the study area. Pohlia richardsii from Costa Rica is a new synonym of P. apolensis. P. longipedicellata from Venezuela and P. verrucosa from Bolivia are new synonyms of P. papillosa. The identity of Bryum anisodontacum, nom. nud., from Chile is clarified and this name is placed in synonymy with P. papillosa. New lectotypes are proposed. Taxonomically important characters of American Pohlia species are reviewed.